PENGARUH WISATA EDUKASI TERHADAP MINAT BERKUNJUNG KEMBALI WISATAWAN KE MUSUEM BAHARI - Jonsen; Dewanta Facrureza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Jakarta Maritime Museum is a maritime-focused gallery located in the Pasar Ikan area of North Jakarta. There has been a significant decline in visitor numbers. This study aims to explore the influence of various educational tours on return visits to the Jakarta Maritime Museum. The approach used in this study is quantitative analysis. Sampling was conducted from the population using a non-probability sampling method with a purposive sampling technique involving 100 respondents. The research methods included classical assumption testing, hypothesis testing, and validity and reliability tests. The research findings indicate that educational tours have a significant influence on visitor satisfaction simultaneously. The test results obtained a coefficient of determination of 96.6%, indicating that educational tours have a 96.6% influence on return visits. The more optimal the implementation of educational tours, including information delivery, educational interactions, supporting facilities, and learning experiences, the greater the return visits. Therefore, the management of the Jakarta Maritime Museum is expected to continue improving the quality of educational tour programs to attract and maintain visitor interest.